Monitoring Extent of Mangroves in Coastal Bangladesh from 1980 to 2020: A Remote Sensing-Based Geospatial Analysis - Muhammad Al-Amin Hoque; Maliha Sanzana Misty; Khandaker Tanvir Hossain; Sharif A. Mukul (Small-scale Forestry, 2026)
Mangrove ecosystems play a vital role in coastal protection, biodiversity conservation, and climate regulation, yet their spatiotemporal dynamics within highly geomorphologically active deltaic environments remain insufficiently understood. This study aimed to map long-term changes in mangrove distribution, quantify mangrove gain and loss patterns, identify dominant land-cover transition pathways, and evaluate the influence of erosion–accretion processes on mangrove dynamics in the Meghna Estuary of coastal Bangladesh using a remote sensing-based geospatial framework spanning 1980–2020. Multi-temporal Landsat imagery was processed through standardized pre-processing, NDVI analysis, and supervised Maximum Likelihood land-use/land-cover classification to quantify mangrove extent, spatial trajectories, and gain–loss dynamics. Post-classification change detection and trajectory analysis were employed to evaluate transitions between mangrove, waterbody, vegetation, and agricultural classes. Results reveal a highly dynamic coastal system characterized by alternating phases of mangrove expansion and contraction primarily driven by erosion–accretion processes. Mangrove cover exhibited a net increase of 158.9 km 2 over four decades, with major gains occurred during 1990–1995 and 2000–2005, primarily due to sediment deposition and natural colonization on newly formed mudflats. Conversely, notable declines between 2005 and 2016 were associated with shoreline erosion and channel migration. Land-trajectory analysis highlights dominant waterbody-to-mangrove transitions, emphasizing the importance of geomorphological processes in shaping ecosystem regeneration and resilience. Despite overall expansion, continuous spatial redistribution indicates ecosystem fragility, with gains concentrated on accretion-prone surfaces and losses along erosion-prone margins. The findings provide the first comprehensive four-decade spatial assessment of mangrove dynamics in the Meghna Estuary, offering critical evidence for adaptive coastal management, ecosystem restoration, and nature-based climate mitigation in Bangladesh.

A Social Forestry Business Framework for Revitalizing Stagnant Forest Farmer Groups: A Case Study from Central Java, Indonesia - Muhammad Abdul Rahman Subrata; San Afri Awang; Ris Hadi Purwanto; Shita Aiswarya; Alvera Wulandhanik; Wahyu Andayani (Small-scale Forestry, 2026)

Only a Noise? The Role of Non-governmental Organizations in the Policy Processes of a New Social Forestry Model in Indonesia - Sari Rahayu; Dwi Laraswati; Dwiko B. Permadi; Muhammad A. K. Sahide; Ahmad Maryudi (Small-scale Forestry, 2023)

The Transition from Arid Farming Systems to Agroforestry Systems in Pakistan: A Comparison of Monetary Returns - Ghulam Abbas; Akhter Ali; Muhammad Khan; Hafiz Zahid Mahmood; Sazali Abdul Wahab; Rafi Amir-ud-Din (Small-scale Forestry, 2021)

Farmer’s Perception of and Factors Influencing Agroforestry Practices in the Indus River Basin, Pakistan - Muhammad Imran Mahmood; Muhammad Zubair (Small-scale Forestry, 2020)

Agroforestry Systems as Alternative Land-Use Options in the Arid Zone of Thal, Pakistan - Muhammad Khan; Hafiz Zahid Mahmood; Ghulam Abbas; Christos A. Damalas (Small-scale Forestry, 2017)

Agroforestry for Livelihood Security in Agrarian Landscapes of the Padma Floodplain in Bangladesh - Syed Ajijur Rahman; Muhammad Hasan Imam; Denyse J. Snelder; Terry Sunderland (Small-scale Forestry, 2012)